Violence against women: characterization of cases registered in the state of Maranhão/Brazil, 2011-2019 - Oliveira, Mag Gardênya Rodrigues; Dantas, Janayra Rodrigues; Conceição, Haylane Nunes da; Cardoso, Guida Graziela Santos; Conceição, Hayla Nunes da; Silva, Ítalo Rafael Costa (O Mundo da Saúde, 2023)
Violence against women is considered a public health problem due to its magnitude and transcendence in the world. Thus, studies on the subject are relevant to support the creation of actions toward prevention, the reduction of cases, and care for victims. The objective of this study was to analyze cases of violence against women in the state of Maranhão, from 2011 to 2019. This is a descriptive, cross-sectional, ecological study with a quantitative approach, carried out from secondary data of notifications of violence against women of reproductive age (10 to 49 years old), obtained from the Notifiable Diseases Information System of the Department of Informatics of the Unified Health System. A total of 12,275 cases were registered in the state, with a predominance of victimization episodes among women aged 20 to 29 years (n=3,863; 31.5%), of mixed race (n=8,883; 72.4%), and with an education between the 5th and 8th grades of elementary school (n= 3,200; 26.1%). There was a predominance of violence against women perpetrated repeatedly (n= 4,784; 39.0%), occurring in the victim’s residence (n= 8,374; 68.2%), practiced mainly in the form of physical violence ( n= 8,239; 67.1%), and having an intimate partner as the main perpetrator. In addition, there was a high number of blank fields in the information regarding the referral of the victim to the healthcare sector. The results presented show the relevance of violence against women, its prevalence, recurrence, and severity in the state of Maranhão, highlighting the need for more effective interventions.